Analisis Kepuasan Pengunjung Terhadap Sarana Transportasi Pulau Putri Kabupaten Bangka - Egy Tiansyah; Andi Gustomi; Sudirman Adibrata (Journal of Tropical Marine Science, 2020)
Satisfaction is one of the important factors that must be considered by someone in order to satisfy consumers. Service quality has five dimensions which include direct evidence (tangibles), reliability, responsiveness (responsiveness), assurance (assurance) and empathy (empathy). The purpose of this study was to analyze the level of visitor satisfaction with the transportation services of Pulau Putri, Bangka Regency. The population of this study were visitors to Pulau Putri who used the services of crossing transportation, with a total sample of 41 respondents. The data collection methods used were observation and interviews. Interview using a questionnaire (questionnaire) which is asked to visitors to Pulau Putri besides the documentation method. The data analysis used is multiple linear regression analysis. The results showed the quality of service which includes direct evidence, reliability, responsiveness, guarantee that the value of Y = 0.22+ 0.58X1 + 0.04X2 - 0.14X3 - 0.11X4 + 0.62X5 is obtained. The direct evidence variable (X1), the reliability variable (X2), and the empathy variable (X5) have a positive and significant effect on visitor satisfaction, while the responsiveness variable (X3) and the guarantee variable (X4) have a negative effect on visitor satisfaction at Pulau Putri Regency, Bangka. Keywords: Satisfaction, Service Quality, Means of Transportation